Modernized Forest Fire Risk Assessment Model Based on the Case Study of three Portuguese Municipalities Frequently Affected by Forest Fires - Santos, Luis (2021)
The number of forest fires ignitions has decreased worldwide, thus observing increased levels of intensity and destruction, endangering urban areas and causing material damages and deaths (Portugal, 2017). Forest fire hazard mapping supported by the surveillance strategy targeted at very susceptible areas with high losses potential are the common tools of fire prevention. Each municipality creates its own Forest Fire Hazard Map, and so it is observed that along the administrative boundaries, discrepancies occur, even when identical types of land use are in place. The evolution of geographic information systems technology sustained by the open-source satellite imagery, along with the innovative Habitat Risk Assessment model of the InVEST software, allowed the creation of an easily applicable trans-administrative boundary fire hazard map, with frequent update capabilities and fully open source. This work considered three municipalities (Tomar, Ourém, and Ferreira do Zêzere) that annually observe various forest fire occurrences. Results enabled the creation of a homogeneous Forest Fire Risk Map, using landuse, slope, road access network, fire ignitions’ history, visualization basins, and the Normalized Difference Vegetation Index (NDVI) as variables. All variables correlate with each other using different weights, in which the different classes of land use are considered as habitats and the remaining variables as fire hazard stressors. The results produce a coherent monthly updated Risk Map, which is an alternative to many risk assessment systems used worldwide.